2021
DOI: 10.1007/s40843-021-1770-0
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated antibacterial red-carbon dots with photodynamic therapy against multidrug-resistant Acinetobacter baumannii

Abstract: The emergence of antibiotic resistance in bacteria is a major public-health issue. Synthesis of efficient antibiotic-free material is very important for fighting bacterial infection-related diseases. Herein, red-carbon dots (R-CDs) with a broad range of spectral absorption (350–700 nm) from organic bactericides or intermediates were synthesized through a solvothermal route. The prepared R-CDs not only had intrinsic antibacterial activities, but also could kill multidrug-resistant bacteria (multidrug-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…As a zero-dimensional nanomaterial, small-sized FDCDs easily stick to the bacterial surface, penetrate the plasma membrane, and lead to damages to intracellular biomolecules [ 43 , 47 , 56 58 ]. Moreover, Liu, et al revealed that the CDs could generate 1 O 2 , whereas the intrinsically antibacterial activity of CDs is also vital [ 59 ]. In our study, negatively charged FDCDs induced the formation of extracellular/intracellular ROS, which lead to the increase of oxidative stress to destroy intracellular biomolecules and then killed bacteria [ 60 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a zero-dimensional nanomaterial, small-sized FDCDs easily stick to the bacterial surface, penetrate the plasma membrane, and lead to damages to intracellular biomolecules [ 43 , 47 , 56 58 ]. Moreover, Liu, et al revealed that the CDs could generate 1 O 2 , whereas the intrinsically antibacterial activity of CDs is also vital [ 59 ]. In our study, negatively charged FDCDs induced the formation of extracellular/intracellular ROS, which lead to the increase of oxidative stress to destroy intracellular biomolecules and then killed bacteria [ 60 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial CDs have also been developed by using traditional antibiotics and common antibacterial compounds as the raw materials to trade the old for the new, such as kanamycin sulfate [ 72 ], levofloxacin hydrochloride [ 73 , 74 ], quaternary ammonium compounds [ 22 , 48 , 49 , 75 , 76 ], and 2,4-dihydroxybenzoic acid [ 77 ]. Luo et al prepared CDs (termed CDs-Kan) from kanamycin sulfate by a one-step hydrothermal method [ 72 ].…”
Section: Antimicrobial Cdsmentioning
confidence: 99%
“…Beyond bare CDs fabricated from mushroom [ 81 ], graphite rods [ 82 ], and the poloxamer Pluronic F-68 [ 83 ], as summarized in our previous review [ 16 ], more bare CDs have been reported to possess intrinsic photodynamic characteristics, including graphitic carbon nitride quantum dots (g-CNQDs) [ 84 ], red-emitting CDs (R-CDs) [ 77 ], CQDs constructed from citric acid and 1,5-diaminonaphthalene by solvothermal reaction [ 85 ], nitrogen- and/or sulfur-doped CDs derived from amino acids [ 43 ], nitrogen and iodine co-doped CDs (N/I-CD) prepared by hydrothermal treatment of iohexol [ 86 ], metal-doped CDs such as zinc-doped CDs [ 87 ], copper-doped CDs [ 88 ], and terbium-doped CDs [ 89 ]. Yadav et al constructed green-fluorescent g-CNQDs from melamine and ethylene diamine tetraacetic acid (EDTA) sodium salt via a thermal polymerization method [ 84 ].…”
Section: Antimicrobial Cdsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 However, efficient ROS generation heavily relies on the proximity between nano-materials and bacteria and is limited by insufficient ROS lifespan and diffusion distance. 17,18 Therefore, higher material doses, exogenous substrates such as H 2 O 2 , and the aid of photo-therapy are often needed to further enhance the anti-bacterial efficacy of the nano-enzymes, 19,20 which introduces multiple components. A few recent studies have improved the bacterial binding and ROS generation ability of nano-constructs by the morphology design and defect engineering of nano-enzymes.…”
Section: Introductionmentioning
confidence: 99%